Esophageal Squamous Papillomatosis Associated Low-Grade Dysplasia Treated with Endoscopic Submucosal Dissection - Buyruk, Abdullah Murat; Erdoğan, Çağdaş (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Murat Buyruk A, Erdoğan Ç. Esophageal squamous papillomatosis associated with low grade dysplasia treated with endoscopic submucosal dissection. Turk J Gastroenterol. 2024;35(9):752-754.